Cork stoppers supply chain: potential scenarios for environmental impact reduction - Demertzi, Martha (2020)
The purpose of the present study is to evaluate the environmental impacts deriving from the production of natural cork stoppers in Portugal, in order to identify the most significant stages and processes (hotspots) and to suggest improvement actions and alternative scenarios. Life Cycle Assessment (LCA) methodology is used by applying a cradle-to-bottling approach. This approach includes the stages of forest management (not considered in related LCA studies), cork preparation, natural cork stoppers production, finishing and distribution to the bottling locations. The results show that the forest management stage has the largest contribution to the environmental impact of natural cork stoppers in the majority of the impact categories. More specifically, the greatest influence derives from the operations of pruning and spontaneous vegetation cleaning. Additionally, the preparation stage and the production stage influence two impact categories each, while the finishing stage is the hotspot in one impact category. These contributions are mainly caused by the energy requirements of these stages. The total environmental impacts may be decreased by 3%–65% if maintenance pruning operations are not performed and simultaneously cleaning operations are undertaken by rotary mowers instead of disc harrows in the forest management stage. Changes in the production stage, such as decreasing the transport distance between the preparation and the production factory or the use of a combination of manual and mechanical punching, do not show great influence in the total environmental impact.